Prevention and screening recommendations in type 2 diabetes: Review and critical appraisal of clinical practice guidelines. Issue 3 (June 2019) - Diab, Mohammad; Barhoosh, Huda A.; Daoudi, Balqis; AlMukdad, Sawsan I.; Zaghloul, Nancy HA.; Ashour, Mayar; Abdelrahman, Iman A.; Paravattil, Bridget; Wilby, Kyle John
Highlights: Recommendations for diabetes prevention and screening lack rigor. Clinicians must appraise recommendations prior to implementation for patient care. Guidelines are strong but have room for improvement with modifications. Abstract: The aim of this review was to identify and appraise guidelines reporting recommendations for the screening and prevention of type 2 diabetes. Five guidelines were included for analysis and all were endorsed by national or international organizations. All guidelines were recommended for practice with or without modifications for both prevention and screening. The overall appraisal scores ranged from 62.5 to 91.7 for prevention and 62.5–83.3 for screening. The highest scored domain was 'clarity of presentation' and the lowest was 'rigor of development'. Findings call for greater attention to rigor when formulating recommendations for prevention and screening of diabetes.